Light-struck taste in white wine: Reaction mechanisms, preventive strategies and future perspectives to preserve wine quality. (June 2021) - Fracassetti, Daniela; Di Canito, Alessandra; Bodon, Rebecca; Messina, Natalia; Vigentini, Ileana; Foschino, Roberto; Tirelli, Antonio
Abstract: Background: The light-dependent reactions involving riboflavin (RF) and methionine (Met) as substrates are responsible for the light-struck taste (LST). This fault is associated to cabbage-like odours due to the formation of methanethiol and dimethyl disulfide impacting negatively on the sensory properties of white wine. The reaction can occur for a relatively short period of time in white wine bottled in clear glass under both natural and artificial lights. Scope and approach: This review aimed to point out the aspects related to the mechanisms of light-dependent reactions and the oenological strategies applicable to counteract the appearance of this detrimental fault. Key findings and conclusions: LST can be prevented through the proper choice of the fermenting yeast, the addition of certain adjuvants being able to remove RF, and additives with a protective effect, such as hydrolysable tannins. As the use of these oenological tools plays an important role in limiting the detrimental change, they represent the strategies applicable in productive approaches. In this context, the more recent findings are summarized also to update the knowledge about the complex reaction mechanisms allowing to overcome the formation of this fault and supporting the wine industry. Highlights: Light-struck taste is detrimental for the sensory profile of white wine. Sulfur compounds are produced from the reaction between riboflavin and methionine. Fermenting yeast plays the major role on riboflavin content in wine. Riboflavin depletion can be obtained with wine treatment with fining agents. Tannins can represent an effective tool against the light-struck taste.